PENDIDIKAN PRIBADI TANGGUH MENUJU PANGGILAN PUBLIK - Agus, Agus (Statement: Jurnal Media Informasi Sosial dan Pendidikan, 2024)
In order to realize the strengthening of self-capacity towards public calling, it is necessary to develop adequate, qualified and qur'ani self-capacity. This study aims to describe and analyze Surah Al Muzamil verses 1-14. This study uses a qualitative research method with a descriptive analysis approach. The focus of the research is strengthening self-capacity towards public calling (analysis of the Qur'an Surah Al Muzammil verses 1-14). The results of this study are strengthening self-capacity by getting used to getting closer to Allah SWT, through the medium of night prayer (tahajjud), if you want to start an activity so you can feel the presence of Allah SWT. As for other media, to build self-capacity is to do remembrance, put your trust, be optimistic, sincere, sincere, patient and istiqomah. Then also each individual must be able to build selfawareness